Proceedings of the Social and Humaniora Research Symposium (SoRes 2018) 2019
DOI: 10.2991/sores-18.2019.120
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Scabies in Religious Boarding School (Pesantren)

Abstract: Scabies is a skin disease that is still a problem with 200 million cases in 2015 in the world. Reducing the incidence of scabies, the understanding of scabies is essential since knowledge is a factor that will determine behaviour. This study aims to analyse the relationship between scabies and the level of knowledge of students in a religious boarding school. This study was a cross-sectional study with analysis using the Fisher Exact test. The incidence of scabies gathered through physical examination, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
(10 reference statements)
0
5
0
2
Order By: Relevance
“…Penyakit kulit merupakan masalah kesehatan yang umum ditemukan dalam lingkungan pesantren, di mana para santri mengalami kontak erat satu sama lain dalam frekuensi yang tinggi dan sering melalaikan aspek kebersihan pribadi di dalam interaksi tersebut. [1][2][3][4] Tak terkecuali di Pesantren Tahfidzul Qur'an Kaffah Al-Mundzirin yang merupakan mitra Program Pembibitan Penghafal Al-Qur'an (PPPA) Daarul Qur'an Palembang, di mana pernah ditemukan kasus serius dari penyakit skabies yang menimpa salah satu santrinya (lihat Gambar 1). Selain itu, survei internal PPPA Daarul Qur'an juga menemukan bahwa ada masalah dalam penanganan sampah di lingkungan pesantren mitra dan pesantren binaannya.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Penyakit kulit merupakan masalah kesehatan yang umum ditemukan dalam lingkungan pesantren, di mana para santri mengalami kontak erat satu sama lain dalam frekuensi yang tinggi dan sering melalaikan aspek kebersihan pribadi di dalam interaksi tersebut. [1][2][3][4] Tak terkecuali di Pesantren Tahfidzul Qur'an Kaffah Al-Mundzirin yang merupakan mitra Program Pembibitan Penghafal Al-Qur'an (PPPA) Daarul Qur'an Palembang, di mana pernah ditemukan kasus serius dari penyakit skabies yang menimpa salah satu santrinya (lihat Gambar 1). Selain itu, survei internal PPPA Daarul Qur'an juga menemukan bahwa ada masalah dalam penanganan sampah di lingkungan pesantren mitra dan pesantren binaannya.…”
Section: Pendahuluanunclassified
“…[1][2] Penyebaran penyakit skabies umumnya terjadi di tempat dengan kepadatan penduduk yang tinggi dan sering terjadi kontak fisik antara satu dengan yang lain, seperti pada lingkungan pesantren. [3][4][5] Penyuluhan adalah sebuah upaya untuk mengubah perilaku manusia dengan pendekatan edukatif melalui kegiatan yang terencana, terarah, dan sistematik dengan kebersihan tubuh dengan rutin, dan menjaga kebersihan lingkungan. [1][2] Kegiatan dilanjutkan dengan pelatihan pembuatan sabun dari minyak jelantah yang dipandu oleh Dr.Eng.…”
Section: Tinjauan Pustakaunclassified
“…The percentage between women and men is almost similar. 12 In 2018, there were 48 patients diagnosed with scabies, consisted of 34 new cases and 14 old cases, who visited Skin and Genital Disease Polyclinic, M. Djamil Public Hospital. While, the incidence of scabies until May 2019 was 12 cases.…”
Section: Issn: 2319-7706 Volume 10 Number 07 (2021)mentioning
confidence: 99%
“…The prevalence of scabies in the general population is 18.5% in Fuji and tends to be higher in children (43.6%) (Romani et al, 2015). Until now, the prevalence of scabies in certain boarding schools is still high, reaching 54.7% of 53 people (Hilma & Ghazali, 2014) and even 85% of 52 people (Tresnasari et al, 2018). In other boarding schools, it has greatly decreased, like a study in Kulon Progo which found the prevalence of scabies in urban and rural boarding schools of 0% and 2% with a population of 30-40 people (Aminjati & Estri, 2014) and 5,3% in the boarding school of Kendal (Ratnaningrum & Avidah, 2020).…”
Section: Introductionmentioning
confidence: 99%